Versatile chemistry of six-membered NHC with boranes: bromination at sp(3) borane, activation of the B-H bond of HBpin, and ring expansion of NHC - Kundu, Gargi; Dixit, Ruchi; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2022)
The NHC.borane chemistry has been majorly restricted to imidazol-2-ylidene classes of carbenes. In our previous communication, we reported the synthesis of 6-SIDipp center dot BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene] and its electrophilic substitution reaction with iodine. Here, we have shown selective bromination of a 6-SIDipp stabilized sp(3) B-H bond. Treatment of 1.2 equivalents of N-bromosuccinamide with 6-SIDipp center dot BH3 gives a mixture of mono- and disubstituted products 6-SIDipp center dot BH2Br (1) and 6-SIDipp center dot BHBr2 (2). However, the reactions with alkyl bromides or carbon tetrabromide resulted in 6-SIDipp center dot BH2Br (1) selectively. Exploration of the chemistry of 6-SIDipp with BHCl2 and 9-BBN (9-borabicyclo[3.3.1]nonane) led to mono-6-SIDipp adducts 3 and 6a. Furthermore, 6a undergoes ring expansion to afford a seven-membered product, 6b, under mild conditions. Unlike BHCl2 or 9-BBN, the B-H bond of HBpin undergoes oxidative addition upon reaction with 6-SIDipp, epitomizing the first example (7) of a B-H bond insertion at NHCs. The analogous reactivity with HBcat led to a tetra-hydropyrimidinium salt with B(cat)(2) as a counteranion (8).

Visible-light-active unsymmetrical squaraine dyes with 1 V of open-circuit voltage for dye-sensitized solar cells - Singh, Amrita; Kumar Singh, Ambarish; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ChemPhotoChem, 2023)
A series of alkyl-group-functionalized, aniline- and indoline-donor-based, unsymmetrical visible-light-active squaraine dyes, AM1-3, were designed and synthesized. Dye-sensitized solar cell (DSSC) devices were fabricated with both I-/I-3(-) and [Cu(tmby)(2)](+/2+) electrolytes. DSSC devices sensitized with the AM1 and AM2 dyes showed relatively high-power conversion efficiency of 7.44 % and 7.22 %, respectively with I-/I-3(-) in the absence of chenodeoxycholic acid (CDCA) than those of the AM3 dye (5.41 %). The [Cu(tmby)(2)](+/2+) electrolyte along with poly(3,4-ethylenedioxythiophene) (PEDOT) as cathode material showed excellent open-circuit potentials (V-OC) of 1030, 1025, and 1001 mV with the DSSC efficiency of 8.05 %, 7.96 %, and 5.84 %, respectively, for the AM1, AM2, and AM3 dyes in the absence of CDCA. Here, the AM1 dye exhibited the maximum DSSC efficiency of 8.05 % and V-OC of 1030 mV, which is the highest obtained efficiency and V-OC for the visible-light active zwitterionic unsymmetrical-squaraine dye with copper-based electrolyte.
Keywords: Cu electrolytes; dihedral angle; Dye-sensitized solar cells; open circuit voltage; squaraine dyes

Visible, far-red, and near-infrared active unsymmetrical squaraine dyes based on extended conjugation within the polymethine framework for dye-sensitized solar cells - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Alkyl group wrapped visible, far-red, and NIR active unsymmetrical squaraine dyes with pi-extension in the polymethine framework-based AM4-AM7 have been designed, synthesized, and utilized as sensitizers for dye-sensitized solar cells. To extend the pi-conjugation within the polymethine framework, thiophene moieties have been incorporated between the donor and acceptor moieties. Absorption spectroscopic studies revealed that pi-extension with each -C & boxH;C- unit resulted similar to 100 nm of redshift in the charge transfer transition with the lambda(maximum) of 541, 643, 747, and 833 nm for AM4, AM5, AM6, and AM7 dyes, respectively, with the molar extinction coefficient of >10(5) M(-1)cm(-1). The pi-extended conjugation-based AM6 and AM7 dyes showed improved light-harvesting efficiency (LHE), where the AM7 dye showed an LHE of 386 nm at 60%. Electrochemical studies of AM dyes revealed that the HOMO energy level of the sensitizers has been modulated systematically. Further, pi-extension within the polymethine framework showed a dramatic effect on V-OC, J(SC), and device efficiency when move from visible active AM4 to far-red active to NIR active AM7 dyes. The DSSC efficiencies of 7.35, 5.18, 0.08, and 0.053% have been achieved with the I-/I-3(-) electrolyte (Z-50) for the AM4, AM5, AM6, and AM7 dyes, respectively. Further, AM4 dye has been cosensitized with AM5, AM6, and AM7 dyes, where AM4:AM5 (1:1) composition achieved the maximum efficiency of 8.12% with I-/I-3(-) electrolyte (Z-50) compared to the other cosensitization compositions.
Keywords: aggregation of dyes; DSSC device efficiency; light-harvesting efficiency; pi-extension; polymethine framework; squaraine dyes